Assessing the status of locus of control as an indicator of core self-evaluations. (February 2016) - Johnson, Russell E.; Rosen, Christopher C.; Chang, Chu-Hsiang (Daisy); Lin, Szu-Han (Joanna)
Abstract: Although core self-evaluation (CSE) is a significant personality predictor of work outcomes, additional research that assesses the structural validity of CSE is needed. It has been suggested that the inclusion of locus of control may have biased past CSE findings because this trait is better suited as a core evaluation of the environment. We investigated this issue in the current study. In Studies 1 and 2 we assessed the factor structure of the CSE factor after controlling for common method variance, which is a salient threat to the validity of higher-order constructs. We found that locus of control no longer loaded on CSE when we controlled for social desirability (Study 1) and when the traits were measured at different times (Study 2). To directly test whether locus of control is better suited as a core evaluation of the environment, in Study 3 we primed 110 employees to think about the predictability of their work environment. Results of this experiment revealed that ratings of locus of control changed as a function of the environment-based manipulation, whereas ratings of the other traits did not. Our research suggests that locus of control may not be an appropriate indicator of CSE. Highlights: We investigate whether locus of control is a core evaluation of the self or environment. Locus of control does not load on CSE after removing common method variance. Perceptions of the environment impact locus of control but not the other CSE traits.